Social Isolation and Associated Factors in Chinese Adults With Epilepsy: A Cross-Sectional Study - Zhong, Rui; Zhang, Hanyu; Chen, Qingling; Guo, Xin; Han, Yujian; Lin, Weihong (Frontiers in Neurology, 2022)
Abstract Objective: We aimed to determine the prevalence of social isolation and associated factors among adults with epilepsy in northeast China. Methods: A cohort of consecutive patients with epilepsy (PWE) from the First Hospital of Jilin University (Changchun, China) was recruited. Demographic and clinical data for each patient were collected during a face-to-face interview. Social isolation was measured using the Berkman-Syme Social Network Index, and the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E) and Quality of Life in Epilepsy Inventory (QOLIE-31) were also administered. Multivariate logistic regression analyses were used to determine the factors associated with social isolation in PWE. Results: A total of 165 patients were included in the final analysis. The mean SNI score was 2.56 (SD: 1.19), and 35 patients (21.2%) were socially isolated. In multivariate logistic regression analysis, higher depressive symptom levels (OR=1.15, 95% CI: 1.003-1.318, P=0.045) and poorer quality of life (OR = 0.967, 95% CI: 0.935-0.999, P=0.047) emerged as independent factors associated with social isolation in PWE. Conclusion: Social isolation is common and occurs in approximately one-fifth of PWE. Social isolation is significantly associated with depressive symptoms and poor quality of life in PWE. Patients need to be encouraged to actively integrate with others and reduce social isolation, which may help improve their quality of life.